O debate sobre avaliação da qualidade na educação infantil: traçando cartografias - Louveira, Andreina de Melo (2015)
This research integrates design Municipal Public Policy Children's Education: diagnosis and research, OBEDUC program (Education Observatory). Funded by CAPES, this dissertation aims to investigate and identify the different theoretical and methodological approaches of what was produced in Brazil from 1993 to 2013, within of 'evaluation' of 'quality' in Early Childhood Education (ECE). To understand the production of 'quality' as a social construction within the concept "will to truth", was used as the theoretical framework of assumptions Foucault (2012, 1988, 1979) on power relations and building a "want to know". As a methodological direction, avail ourselves of the construction of the concept of 'quality' from cartography, which provides the ability to understand it as a social invention without subjecting the linear temporal dimensions as key facts and lets think of it as a cross concept forces of relationships that need to be considered to achieve their size (BARROS; KASTRUP, 2010). This research was divided into three phases: the first involves the description of the process of looking for work in digital databases through the descriptors evaluation , quality and early childhood education . The selected databases were SciELO (Scientific Electronic Library Online), Anped (National Association of Graduate Studies and Research in Education), BDTD (Brazilian Digital Library of Theses and Dissertations), Ana Maria Poppovic Library (BAMP) of the Carlos Chagas Foundation (FCC) and CAPES Journal. The second phase describes the process of organization and construction of thematic groupings for analysis, guided by a roadmap of features for reading that allowed grouping the research, according to their theoretical and methodological similarities. The third phase presents the explanation of each research from the perspective of their respective group and discusses the main theoretical directions that permeate its construction. In total, we analyzed 43 studies that evidence the main theoretical and methodological approaches that have built the evaluation of the 'quality' in ECE, particularly from the perspective of environmental psychology, the use of environment assessment scales and as a preparation for teaching fundamental. We believe that the 'quality' as a social invention is constructed as a political activity in the primary sense of the term, that is, as an activity that organizes and directs the Early Childhood Education.